RVIEW OF NON-DESTRUCTIVE ANALYSIS METHODS AND THEIR APPLICATION FOR MONITORING THE DURABILITY OF CONCRETE STRUCTURES - MONZHERAN, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
An overview of non-destructive methods (NDM) of analyzing the structural integrity and durability of concrete structures, their advantages and disadvantages and use to assess the condition of structures under the influences of aggressive environments. The need to select core samples for predicting the durability of concrete structures has been established. Presented methods: phenolphthalein reaction to the depth of penetration of carbonization of concrete, determination of strength by the method of elastic rebound using a Schmidt hammer, ultrasonic analysis of the integrity of the structure, determination of strength by the method of detachment with chipping, electrical methods of corrosion analysis of reinforced concrete structures. The selection of samples, effectively serves for external assessment of existing deformations, the quality of concrete composition formation and the strength measurements. The method of phenolphthalein reaction can be effectively applied directly on fresh samples and at the place of sampling. The elastic rebound method is the most common due to its simplicity and high transportability of the main equipment - the Schmidt hammer. The requirements for the exploitability of the device (hammer) and the surface of the structure requires the presence of calculated transfer coefficients to determine strength. The method of detachment with chipping is effective and the least destructive NDM. It takes into account the influence of an aggressive environment on the structure, yet, it is insufficient to assess internal changes in the structure. The method of ultrasonic analysis and electrical monitoring of corrosion reveals deviations in the integrity of the structure in the absence of obvious external damage and allows to calculate the degree of damage.